High efficiency solar air heater - Mohamad, AA (Pergamon-Elsevier Science Ltd, 1997)
This article presents an analysis for a novel type of solar air heater. The main idea is to minimize heat losses from the front cover of the collector and to maximize heat extraction from the absorber. This can be done by forcing air to how over the front glass cover (preheat the air) before passing through the absorber. Hence, this design needs an extra cover to form a counter-flow heat exchanger. Porous media forms an extensive area for heat transfer, where the volumetric heat transfer coefficient is very high. Hence, using a porous absorber will enhance heat transfer from the absorber to the airstream. In the design of this type of collector, which combines double air passage and porous media, care should be taken to minimize pressure drop. However, the thermal efficiency of this type of collector is significantly higher than the thermal efficiency of conventional air heaters. The thermal efficiency of the suggested collector exceeds 75% under normal operating conditions. The pressure drop is not so significant if high porous medium is used and careful design of U-return section is considered. (C) 1997 Elsevier Science Ltd.
Keywords: Packed-Bed